Fracture resistance of restorations with fiber-reinforced composites: systematic analysis - Escobar, Lorena Cristina Bogado (2023)
Aims: This study aimed to evaluate and compare the fracture resistance values of composed/complex fiber-reinforced composite restorations, in posterior teeth, with those of healthy teeth, or of non-fiber-reinforced composites restorations or, of unrestored cavity preparations by means of an in vitro outputs systematic quantitative and qualitative analysis. Methodology: Methodic search was performed using PubMed, Web of Science and Google Scholar from 15th may to 12th June 2023. Only in vitro studies published as articles in English idiom in the last 10 years, and that evaluate/compared the fracture resistance values of human posterior teeth with extensive fiber-reinforced composite restorations, with those of healthy teeth, or of non-fiber-reinforced composites restorations or, of unrestored cavity preparations were included. This study was registered (425509) in PROSPERO database and followed the PRISMA guidelines. The risk of bias assessed by The QUIN tool. The fracture resistance median values, in Newton (N), were calculated for all, experimental and control groups with a 95% confidence interval. For pairwise comparation nonparametric tests (<0.05) were applied. Results: From 932 articles obtained, only 24 publications met the inclusion criteria; 23 had moderate and one high risk of bias. Overall fracture resistance of experimental group median value was of 976.0 N and differ from all control groups. Pairwise comparison revealed that experimental group showed lower values of fracture when compared with healthy teeth (1459.9; p=0.048) but higher than those of two control groups, composite non-fiber-reinforced restoration (771.0 N; p=0.008) and cavity preparation without restoration (386.6 N; p<0.001). Conclusion: In vitro systematic outputs evidenced that glass and/or polyethylene fibers can improve composite restorations fracture resistance values.